Criminal mediation as an alternative to the criminal case in Iraqi legislation - حسين, الاء ناصر; خلف, سحر عباس (Journal of Legal Sciences, 2021)
Criminal mediation is one of the new means that seeks to resolve criminal disputes away from the traditional procedures of criminal cases and outside the court, but under his supervision and supervision, the mediation process is based on the consensual idea of ​​ending the conflict as it gives both the offender and the victim a role in resolving the next conflict between them Outside the judiciary, with the intervention of a third party from the third party (the mediator), who has the main role in the success of the mediation process, and the mediator is obligated to inform the judicial authority of the results of the mediation, and then the judicial authority later has discretion in the return report, otherwise You will either go through or complete the criminal proceedings. Despite the importance of the mediation system and its consistency with the social nature of Iraqi society, as it is a society with interconnected social relations, and this is what helps criminal mediation succeed in disputes, the Iraqi procedural legislation has not been adopted.